P425 Real-world evidence on effectiveness and safety of vedolizumab therapy for inflammatory bowel disease in Taiwan: Results from the TSIBD registry (VIOLET Study). (27th May 2021) - Wei, S C; Lin, W C; Chang, C H; Tu, C H; Feng, I C; Shieh, M J; Chung, C S; Yen, H H; Chou, J W; Tai, W C; Wong, J M; Liu, Y H; et al.
Abstract: Background: GEMINI trials and real-world studies in Western population have demonstrated the effectiveness and safety of vedolizumab (VDZ) for IBD. However, long-term real-world evidence of VDZ in Asian populations remains limited. This study aimed to investigate the effectiveness and safety of VDZ in Taiwan CD and UC patients, and the IBD relapse after VDZ discontinuation. Methods: Data were prospectively collected (January 2018-May 2020) from the Taiwan Society of IBD (TSIBD) registry, one of the largest real-world Asian IBD cohorts. Patients (>18 years old) receiving ≥1 dose of VDZ with up to a 1-year follow-up period were analyzed. Effectiveness at 6 month and 1 year including clinical response (CRS), clinical remission (CRM), steroid-free remission (SRM) and mucosal healing (MH);and safety outcome were analyzed descriptively. IBD relapse after VDZ treatment discontinuation was assessed since the reimbursement period in Taiwan is limited due to drug holiday required by government. Results: A total of 274 patients (CD:127, UC:147) were included. At VDZ initiation, average [SD] age (year): 33.4 [14.6] in CD and 42.4 [14.3] in UC; median disease duration (years): 3.1 in CD and 3.9 in UC; 50.4% of CD and 70.7% of UC patients were biologics (bio)-naïve. Treatment effectiveness was analyzed (Figure 1-4). At 6 months, effectiveness in the CD bio-naïve group was significantly higher than the bio-exposed patients in CRS (67.4% vs 43.9%, p=0.047), CRM (62.8% vs 39.0%, p=0.025), and SRM (43.3% vs 4.3%, p=0.001), respectively. At 1 year, the CD bio-naïve group had higher CRS (82.1% vs 60.7%, p=0.026) than the bio-exposed group. There was no difference in effectiveness between bio-naïve and bio-exposed groups in UC at both 6 months and 1 year. Three patients (1.1%) reported serious infections (respiratory infection, intractable infection with underlying myelodysplastic syndrome and intestinal perforation due to endoscopy) and two (0.7%) had infusion-related reactions. No malignancies or hepatic injuries were reported. After limited treatment up to one year due to reimbursement, 58% (54/93) of patients had IBD relapse (CD: 27 [62.8%], UC: 27 [54%]). After cessation of VDZ, the mean [SD] time to IBD relapse was 5.5 [4.0] months in CD, and 5.8 [5.7] months for UC. Conclusion: This study has shown the effectiveness and safety of VDZ therapy for Taiwan IBD patients. Better outcomes were observed in bio-naïve CD patients, whereas bio-naïve and bio-exposed UC patients have comparable outcomes. After a limited VDZ treatment duration, over one-half of patients had IBD relapse, with the majority occurring within 5 months of VDZ discontinuation. These data suggest that continued VDZ therapy would benefit the majority of IBD patients in Taiwan.